A Simple Vacuum‐Based Microfluidic Technique to Establish High‐Throughput Organs‐On‐Chip and 3D Cell Cultures at the Microscale. Issue 1 (21st September 2018) - Visone, Roberta; Ugolini, Giovanni Stefano; Vinarsky, Vladimir; Penati, Miriam; Redaelli, Alberto; Forte, Giancarlo; Rasponi, Marco
Abstract: Microfluidic‐based 3D cell culture and organs‐on‐chip have proved able to generate accurate in vitro models of human physiology. Their widespread application and adoption are however hampered by limited scalability and throughput. Here, a novel strategy is described to significantly enhance the throughput of microfluidic systems for 3D cell culture and organs‐on‐chips. A series of 3D culture chambers (up to 96 replicates) can be seeded with a single pipetting operation and a system of normally closed microfluidic valves ensures the resulting 3D microtissues are independent. Devices fabricated with this design principle are employed to perform 3D cultures of rat cardiac fibroblasts and profile two known drugs (doxorubicin, sotalol) in terms of cytotoxicity. In addition, human contractile cardiac microtissues is generated using iPSC‐derived cardiac myocytes and functional assays on microtissues calcium transients after treatment with a known chronotropic drug (verapamil) are performed. The systems here described thus open up new perspective in the scalability of organs‐on‐chip and pave the way to multireplicate 3D cell cultures in microfluidics. Abstract : A simple strategy to enhance the throughput of microfluidic systems for 3D cell cultures and organs‐on‐chips is presented. A system of normally closed microfluidic valves ensures the injection of up to 96 replicates and their independent long‐term culture.